The influence of governance of risk management on systemic risk in Indonesian banking for the 2019-2023 Period - Irawan, Panji; Hanggraeni, Dewi (International Journal of Innovative Research and Scientific Studies, 2025)
Indonesian banking plays a vital role in supporting national economic growth. However, the industry is also vulnerable to systemic risks that can undermine national financial stability. This study aims to analyze the influence of governance of risk management on systemic risk in Indonesian banking for the 2019–2023 period, using the Value at Risk (VaR) and Expected Shortfall (ES) measurement approaches. Utilizing a quantitative approach with the panel data regression method, this study examined 32 foreign exchange banks that were selected purposively. The results show that the existence of a Risk Management Committee (RMC) significantly reduces systemic risks, as measured by both the VaR and ES approaches. The use of the variance-covariance estimator (vce) cluster method successfully corrected the weaknesses of the model due to heteroscedasticity and autocorrelation. These findings confirm the importance of a strong risk governance structure in minimizing the impact of the financial crisis. The implications of these results encourage the strengthening of the role of the RMC and the adaptation of bank risk governance to respond to the evolving risk dynamics in the national financial sector.